Muscle Disease : Pathology and Genetics - Goebel, H.-H.; Sewry, Caroline A.; Weller, Roy O.; International Society of Neuropathology (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
This book clarifies the pathology and genetics of muscle disease for pathologists, clinicians, geneticists and researchers to aid in the diagnosis and management of patients. Organized around the 'motor unit' concept, this book presents the latest understanding of muscle disease, and how this can help identify new treatments.
Revision of: Structural and molecular basis of skeletal muscle diseases / volume editor, George Karpati. Basel : ISN Neuropath Press, c2002.
Includes bibliographical references and index.
Print version record.
Keywords: Muscles -- Diseases; Muscular Diseases -- pathology; Muscular Diseases -- genetics; HEALTH & FITNESS -- Diseases -- Musculoskeletal; MEDICAL -- Orthopedics; MEDICAL -- Rheumatology; Muscles -- Diseases; Medicine; Muscular diseases -- Genetics; Muscular diseases -- Pathology; Electronic books; Libros electronicos; Electronic books